SOURCES OF INFORMATION AMONG MEDICAL STUDENTS DURING THE COVID-19 PANDEMIC - Đokić, Milena; Djokic, Ana; Stanisavljevic, Tamara; Milic, Nikola; Milin Lazovic, Jelena (Medicinski podmladak, 2022)
Introduction: Relevant information about COVID-19 is crucial for disease prevention and its spread. The aim of this study was to assess sources of information among medical students during the COVID-19 pandemic. Material and methods: This cross-sectional study was conducted on 373 students of the Faculty of Medicine University of Belgrade. The anonymous questionnaire consisted of 3 parts: socio-demographic characteristics, information sources and the attitude towards available information about COVID-19. Questionnaire was available online during January 2021.Results: At the beginning of the pandemic, most students informed several times a day (37.5%), latter it would drop to beeing informed several times a week (33.8%) (p
Keywords: information, medical students, pandemic, COVID-19